Spatial Morphology and Geographic Adaptability of Traditional Villages in the Hehuang Region, China - Xinhong Zhang; Haiqin Yang; Yuyuan An (Buildings)
Understanding the spatial morphology and geographic adaptability of traditional settlements is crucial for their preservation and management. Accordingly, this study employs Hehuang region, China, as a case study, adopting an integrated approach that combines morphological type analysis and boundary shape index. This comprehensive methodology systematically investigates the spatial morphological features and reveals the geographic adaptability of the two types of traditional villages, which are river valley and mountain types. Specifically, the results demonstrate that: (1) The boundary morphology of river valley-type traditional villages is primarily composite, with a regular and compact overall tendency, creating a spatial pattern consisting of mountains and water bodies surrounding farmland and villages, which conveniently supports agricultural production. Their streets and alleys are mainly fishbone-shaped, dendritic, and grid-shaped. (2) Mountain-type traditional villages also exhibit composite boundary morphology but with lower compactness, higher fragmentation, and more pronounced belt-shape characteristics. Their spatial pattern facilitates agriculture and animal husbandry, with streets and alleys being predominantly grid-shaped, S-shaped, and Z-shaped. (3) The spatial morphology of both types of villages is well-adapted to local terrain and climate conditions, as well as to the resident’s requirements for water use and disaster prevention, which reflects the wisdom of the Hehuang region’s ancestors regarding settlement construction. This study contributes to comprehending the spatial characteristics and geographic adaptability of traditional villages in a multicultural area and provides a significant reference for advancing analogous traditional settlement protections and rural revitalization initiatives.